Άγνωστα Μεγαλυνάρια στον άγιο Νικόλαο του Πατριάρχη Αλεξανδρείας Αθανασίου Β΄ - ΣΤΡΑΤΗΓΟΠΟΥΛΟΣ Δημοσθένης (Byzantina Symmeikta, 2025)
This study presents, for the first time and in a critical edition, the megalynaria to St. Nicholas written by the Patriarch of Alexandria, Athanasius II (ca. 1275-ca.1315). These hymnographical texts are delivered from codex Sinaiticus gr. 669 and prove that the singing of megalynaria to saints had entered the liturgical practice of the Sinai monastery as early as the 14th century.